Use of Polyacrylic Acid and Polydimethylsiloxane Mixture for In‐Needle Microextraction of Volatile Aroma Compounds in Essential Oils. (15th October 2015) - Jeon, Hye‐Lim; Son, Hyun‐Hwa; Bae, Sunyoung; Lee, Dong‐Sun
Abstract : A prototype stainless steel needle (Hamilton 90022, 22 gauge, 718 µm o.d., 413 µm i.d., 51 mm length, bevel tip) packed with polyacrylic acid (PAA) and polydimethylsiloxane (PDMS) mixture (7:3 ratio) having a micro‐bore tunnel (290 µm i.d., ca. 61.5 µm thickness, 10 mm length) was newly prepared as a device of headspace in‐needle microextraction (HS‐INME). Design of the needle, optimization of adsorption, desorption parameters, and validation of analytical methods were conducted to evaluate the HS‐INME efficiency for volatile organic compounds. The optimized adsorption conditions were 60 °C for 20 min and desorption conditions were 240 °C for 2 min. The calibration curves showed good linearity with the squared correlation coefficient value ( r 2 ) over 0.99. The limit of detection for linalool, (+)‐limonene, and eugenol were 13.5, 10.9, and 9.1 ng while limit of quantification were 45.1, 36.4, and 30.5 ng, respectively. The recovery results showed the acceptable range between 95.6 and 115.3%. The relative standard deviations for intra‐ and inter‐assay showed the values less than 10%. It was applied to analyze seven essential oils for polar and nonpolar volatile aroma compounds successfully. From the results obtained in this study, HS‐INME was advantageous to low cost due to ease of fabrication, reuse without loss of absorbent or reduction of extraction efficiency, and no use of solvent. In conclusion, a needle packed with PAA and PDMS mixture having a micro‐bore tunnel is a new development of INME that may complement the shortcomings of the current headspace extraction methods. Abstract :